A Therapeutic Potential of Vitamin D in Asthma Control - Aldona Pażyra; Paweł Stanicki; Julita Szarpak; Natalia Kusak; Natalia Żak; Barbara Jaworska (Kazimierz Wielki University, 2024)
In 2019, according to WHO estimates, 262 million people were affected by asta, resulting in 455,000 deaths. Asthma, is a chronic inflammatory disease of the airways that causes reversible bronchoconstriction, making it difficult for patients to breathe. Exacerbations of the disease can be caused by a variety of factors but share similar symptoms such as wheezing, coughing, shortness of breath and chest tightness. Severe asthma exacerbations are defined as symptoms that do not respond to inhaled medications and improve only after oral or intravenous steroid administration. Asthma-related deaths often occur during exacerbations. Vitamin D, which is produced naturally in the body and found in some foods, is a steroid-derived vitamin. Adequate doses of this vitamin, administered through medication or supplements, can be used to maintain its proper levels in the organism. Vitamin D is essential for regulating calcium levels in the body and for bone remodeling. It also has immunomodulatory effects, affecting both innate and adaptive immunity. This partly explains its association with changes in the airway epithelium that occur as a result of inflammation in asthma. The study aims to summarize the current knowledge on the relationship of vitamin D with asthma symptom control. The present study is based on literature available in scientific databases from 2013-2016, such as PubMed, Corchane Library and Google Scholar, using the following keywords: "vitamin D" and "asthma." Vitamin D deficiency is prevalent in children and adults worldwide. A critical analysis of the literature reveals that the therapeutic administration of vitamin D has no apparent advantage in treating asthma, especially in children. Nevertheless, for adults with mild asthma, vitamin D supplementation shows promise for improved outcomes. However, there is a pressing need for large-scale clinical trials to determine the efficacy and safety of this therapeutic approach for both age groups.